Assessment of changes in nicotine dependence, motivation, and symptoms of anxiety and depression among smokers in the initial process of smoking reduction or cessation: a short-term follow-up study - Figueiró,Luciana Rizzieri (2013)
Introduction: The first days of a quit attempt represent an important challenge to long-term abstinence, especially because of the changes that take place over this period. Objective: To examine whether smokers who have recently changed their smoking behavior show changes in the intensity of nicotine dependence, motivational stage, or symptoms of anxiety and depression relative to smokers without recent changes in smoking behavior. Methods: Smokers attending a support group for smoking cessation in Porto Alegre, southern Brazil, were invited to participate. The program consisted of four weekly sessions. Smokers answered questionnaires covering intensity of nicotine dependence, stage of motivation, and symptoms of anxiety and depression at baseline and in the fourth week. Urine was collected at both time points, tested for cotinine concentration, and used to determine the final status of smokers. Results: Of the 54 smokers included in the study, 20 (37%) stopped smoking or decreased tobacco use. Both smokers who stopped or reduced tobacco use and those who did not change their behavior presented a decrease in nicotine dependence scores (p = 0.001). Conversely, only the smokers who changed behavior presented an increase in scores in the maintenance stage (p < 0.001). Conclusion: When modifying tobacco use, smokers face a difficult process, marked by several changes. A better understanding of these changes and their implications for treatment are discussed.